2021
DOI: 10.3390/v13071400
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responsiveness to Influenza: What Drives It?

Abstract: The induction of a specific antibody response has long been accepted as a serological hallmark of recent infection or antigen exposure. Much of our understanding of the influenza antibody response has been derived from studying antibodies that target the hemagglutinin (HA) protein. However, growing evidence points to limitations associated with this approach. In this review, we aim to highlight the issue of antibody non-responsiveness after influenza virus infection and vaccination. We will then provide an ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 233 publications
(260 reference statements)
0
8
0
Order By: Relevance
“…It has also been suggested that frailty, an aging syndrome affects the antibody response generated by vaccines in elderly people. 18 …”
Section: The Effect Of Age On Vaccine Responsementioning
confidence: 99%
See 3 more Smart Citations
“…It has also been suggested that frailty, an aging syndrome affects the antibody response generated by vaccines in elderly people. 18 …”
Section: The Effect Of Age On Vaccine Responsementioning
confidence: 99%
“…In addition to immune system differences between the sexes, sex‐based disparities in antibody response may be related to the effect of sex hormones and immune regulatory genes on chromosome X, genes such as Tlr7 are located on the sex chromosomes, 18 , 24 and high testosterone levels repress vaccine response in men; however, it is controversial. 18 In short, the role of the sex variable in the vaccine response should be explored in clinical trials.…”
Section: The Role Of Sex Differences In Vaccine Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Tomic, Pollard, and Davis [4] provide a thorough overview of systems' immunology approaches and their role in dissecting immune correlates of protection for influenza to determine the immune interactions for effective viral control and vaccine efficacy. Lin et al [5] focus on the issue of antibody non-responsiveness to influenza infection and vaccination, discussing biological factors that may impact antibody responses and technical factors that may influence their analysis. Bull et al [6] discuss the potential impacts of next-generation vaccines that may be non-sterilizing, leading to increased immune evasion by rapidly mutating influenza viruses.…”
mentioning
confidence: 99%